Why charging Li-air batteries with current low-voltage mediators is slow and singlet oxygen does not explain degradation - Ahn, S; Zor, C; Yang, S; Lagnoni, M; Dewar, D; Nimmo, T; Chau, C; Jenkins, M; Kibler, AJ; Pateman, A; Rees, GJ; Gao, X; et al. (Springer Nature, 2023)
Although Li–air rechargeable batteries offer higher energy densities than lithium-ion batteries, the insulating Li2O2 formed during discharge hinders rapid, efficient re-charging. Redox mediators are used to facilitate Li2O2 oxidation; however, fast kinetics at a low charging voltage are necessary for practical applications and are yet to be achieved. We investigate the mechanism of Li2O2 oxidation by redox mediators. The rate-limiting step is the outer-sphere one-electron oxidation of Li2O2 to LiO2, which follows Marcus theory. The second step is dominated by LiO2 disproportionation, forming mostly triplet-state O2. The yield of singlet-state O2 depends on the redox potential of the mediator in a way that does not correlate with electrolyte degradation, in contrast to earlier views. Our mechanistic understanding explains why current low-voltage mediators (<+3.3 V) fail to deliver high rates (the maximum rate is at +3.74 V) and suggests important mediator design strategies to deliver sufficiently high rates for fast charging at potentials closer to the thermodynamic potential of Li2O2 oxidation (+2.96 V).